2020
DOI: 10.3390/healthcare8030344
|View full text |Cite
|
Sign up to set email alerts
|

Are Individuals Perceived as More Attractive within a Group? A Confirmative Study of Group Attractiveness Effect and the Cheerleader Effect in China

Abstract: The stereotype “what is beautiful is good” suggests that having an attractive physical appearance is very important to people’s lives. Physical attractiveness, as an important personal trait, plays vital roles for shaping one’s first impression, and for influencing one’s subsequent evaluation and selection, based on obvious visual features. However, the contextual difference of the physical attractiveness between a group and its group members has been given less attention. For this reason, Van Osch et al. prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…An effect of assimilation towards the attractiveness of the other group members (Bar-Tal & Saxe, 1976;Wedell et al, 1987) would produce a pattern of results similar to those predicted by hierarchical encoding, which was not supported in the current study. Recently, it has been reported that the number of faces in the group contributes to the size of the cheerleader effect (Peng et al, 2020). However, this finding has been inconsistent (Walker & Vul, 2014) and would not explain why groups of the same size can experience different sized cheerleader effects (Carragher et al, 2019).…”
Section: Other Potential Mechanismsmentioning
confidence: 98%
See 1 more Smart Citation
“…An effect of assimilation towards the attractiveness of the other group members (Bar-Tal & Saxe, 1976;Wedell et al, 1987) would produce a pattern of results similar to those predicted by hierarchical encoding, which was not supported in the current study. Recently, it has been reported that the number of faces in the group contributes to the size of the cheerleader effect (Peng et al, 2020). However, this finding has been inconsistent (Walker & Vul, 2014) and would not explain why groups of the same size can experience different sized cheerleader effects (Carragher et al, 2019).…”
Section: Other Potential Mechanismsmentioning
confidence: 98%
“…The cheerleader effect Facial attractiveness is typically considered to be signalled by physiological characteristics of the face, such as symmetry, averageness, and sexually dimorphic appearance (Little, Jones, & DeBruine, 2011;Rhodes, 2006). Yet, many recent studies have shown that facial attractiveness is also influenced by social context (Carragher, Thomas, Gwinn, & Nicholls, 2019;Furl, 2016;Hsieh et al, 2020;McDowell & Starratt, 2019;van Osch, Blanken, Meijs, & van Wolferen, 2015;Peng, Mao, Pagliaro, Roberts, & Livi, 2020;Walker & Vul, 2014;Ying, Burns, Lin, & Xu, 2019). Many of these studies describe 'the cheerleader effect' (Rashid & Fryman, 2008), which is said to occur when an observer judges the same face to be more attractive in a group compared to when it is seen alone (Walker & Vul, 2014; see also 'friend effect', Ying et al, 2019).…”
mentioning
confidence: 99%